The impact of client and manufacturers role and industrial relationships on construction innovation - Abdul Nifa, Faizatul Akmar; Mohd Nawi, Mohd Nasrun; Hamzah, N. (2006)
Using a suitable shading device's slats, venturi effect can be induced to increase air velocity.In the preliminary experiment, three different variables of widths of the shading device, aperture sizes, and angle of slats have been tested.In this experiment, extensions are attached to the front and rear of the slats.Based on the L9 orthogonal array of the Taguchi method of Design of Experiment, the effect of front and rear extension, and aperture size on the wind flow velocity are studied. A design of experiment (DOE) is the simultaneous evaluation of two or more factors for their ability to affect the resultant average or variability of a particular product or process characteristic.The results of the experiment shows similar trend of velocity profile as in the preliminary experiment.The wind velocity increases significantly at the constriction but drops rapidly as it flows away from the slats.Analysed using the Analysis of Variance (ANOVA), the influential variables and interactions between variables that affect the wind flow velocity, and the optimum conditions are determined.The aperture sizes are found to have greater influence on the result at the point of constriction.